Coupled thermo-hydro-mechanical-chemical modeling on acid fracturing in carbonatite geothermal reservoirs containing a heterogeneous fracture. (July 2021) - Xu, Haoran; Cheng, Jingru; Zhao, Zhihong; Lin, Tianyi; Liu, Guihong; Chen, Sicong
Abstract: Acid fracturing and hydraulic fracturing are two useful methods to improve productivity of geothermal wells. Compared with hydraulic fracturing, it remains challenging to select and design an optimal scheme of acid fracturing in geotherm reservoirs due to the complex chemical reactions between acidizing fluids and reservoir rocks. A modeling framework for the coupled thermal-hydro-mechanical-chemical processes during acid fracturing in carbonatite geothermal reservoirs is developed, which is verified using the published experimental results. Effects of natural and human-controlled factors on efficiency of acid fracturing are investigated through parameter sensitivity analysis. The results show that the two human-controlled parameters including acid concentration and injection rate play an important role in determining propagation area, whereas the acid etching pattern is mainly dependent on natural reservoir parameters including aperture field, reservoir temperature and in-situ stress. The developed modeling framework is successfully applied to simulate a field test of acid fracturing in a geothermal well, Beijing, China. The further follow-up research and limitations of the present study are also addressed. Highlights: A coupled THMC modeling method of acid fracturing in geothermal fields is developed. The roles of natural and human factors in efficiency of acid fracturing are studied. The modeling method successfully predicts the results of acid fracturing field test.